2009
DOI: 10.1016/j.jcrs.2008.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Case of late-onset corneal decompensation after iris-fixated phakic intraocular lens implantation

Abstract: A 48-year-old myopic patient with bilateral anterior chamber depth of 3.1 mm and endothelial cell density (ECD) of 2525 cells/mm(2) and 2638 cells/mm(2) preoperatively had bilateral implantation of an Artisan iris-fixated phakic intraocular lens (pIOL). Five years postoperatively, unilateral corneal stromal edema was seen in a circumscribed area overlying the temporal ridge of the pIOL in the right eye; the ECD was 1631 cells/mm(2) and the pachymetry, 586 microm. Explantation of the pIOL was refused by the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The risk of corneal decompensation following pIOL implantation is well established 2,47,14. Possible mechanisms for endothelial cell loss and decompensation include surgical trauma, early postoperative elevated intraocular pressure, chronic anterior chamber inflammation secondary to the implant, contact between the cornea and the lens haptics, or transient contact between the lens optic and the corneal endothelium 5.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of corneal decompensation following pIOL implantation is well established 2,47,14. Possible mechanisms for endothelial cell loss and decompensation include surgical trauma, early postoperative elevated intraocular pressure, chronic anterior chamber inflammation secondary to the implant, contact between the cornea and the lens haptics, or transient contact between the lens optic and the corneal endothelium 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, corneal decompensation after Artisan IOL implantation has been reported and may have been caused by excessive eye rubbing because of itching or by an anterior shift of the IOL due to its loose fixation to the iris surface. 25,26 Therefore, exact, firm fixation of the IOL in an area with sufficient iris tissue is essential to protect the corneal endothelium. Koss and Kohnen 27 found that the postoperative ACD was shallower in smaller eyes than in longer eyes and suggest performing posterior enclavation of iris-fixated IOLs in smaller eyes to ensure a safe distance between the IOL and the corneal endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the distance between the tube and the cornea was not related to the dropout of the endothelium [18], but intermittent touching of the corneal endothelium due to blinking and rubbing of eyes cannot be ruled out [19]. However, previous studies in phakic intraocular lens patients showed that corneal endothelial dropout is related to the distance between the lens implant and cornea, and they also showed intermittent touching of the corneal endothelium by the intraocular lens [2022]. These patients were highly myopic and tended to have a deeper anterior chamber than many glaucoma patients, and the shunt is more flexible than the intraocular lens.…”
Section: Discussionmentioning
confidence: 99%